NAVOIY VILOYATI MEHNAT RESURSLARINING SHAKLLANISHI VA AHOLI BANDLIGIGA TA’SIR ETUVCHI OMILLAR - Norov, Sh.Sh. (SCIENCE and SOCIETY, 2024)
The article analyzes the factors affecting the formation and employment of Labor resources of the Navoi region, namely, natural geographical factors, economic geographical factors, demographic factors, social geographical factors.